Digital rights management - Van Tassel, Joan. (Amsterdam : Focal Press, 2006)
"Digital rights management (DRM) is a type of server software developed to enable secure distribution - and perhaps more importantly, to disable illegal distribution - of paid content over the Web. DRM technologies are being developed as a means of protection against the online piracy of commercially marketed material, which has proliferated through the widespread use of Napster and other peer-to-peer file exchange programs. With the flourish of these file exchange programs, content owners, creators and producers need to have a plan to distribute their content digitally and protect it at the same time--a seemingly impossible task. There are numerous books dealing with copyright, eBusiness, the Internet, privacy, security, content management, and related technical subjects. Additionally, there are several research papers, and almost daily newspaper and magazine articles dealing with digital piracy. However, there are only a few books and documents that bring these together as a basis for profitable exchange of digital content. Digital Rights Management can help content providers make money by unifying the confusing array of concepts that swirl around current presentations of DRM in newspapers and business publications."--Publisher's description.
1. Industry overview -- 2. Intellectual property and copyright -- 3. The content revolution -- 4. Content protection and digital rights management technologies -- 5. DRM systems : design and implementation -- 6. DRM and entertainment and media business models -- 7. DRM stakes and stakeholders -- 8. Living with DRM.
Includes bibliographical references and index.
Keywords: COPYRIGHT AND ELECTRONIC DATA PROCESSING